Contextual Fear Memory Retrieval Is Vulnerable to Hippocampal Noise. (16th September 2020) - Iwasaki, Satoshi; Ikegaya, Yuji
Abstract: Memory retrieval depends on reactivation of memory engram cells. Inadvertent activation of these cells is expected to cause memory-retrieval failure, but little is known about how noisy activity of memory-irrelevant neurons impacts mnemonic processes. Here, we report that optogenetic nonselective activation of only tens of hippocampal CA1 cells (∼0.01% of the total cells in the CA1 pyramidal cell layer) impairs contextual fear memory recall. Memory recall failure was associated with altered neuronal reactivation in the basolateral amygdala. These results indicate that hippocampal memory retrieval requires strictly regulated activation of a specific neuron ensemble and is easily disrupted by the introduction of noisy CA1 activity, suggesting that reactivating memory engram cells as well as silencing memory-irrelevant neurons are both crucial for memory retrieval.